Soil Microbial Resources for Improving Fertilizers Efficiency in an Integrated Plant Nutrient Management System - Bargaz, Adnane; Lyamlouli, Karim; Chtouki, Mohamed; Zeroual, Youssef; Dhiba, Driss (Frontiers in Microbiology, 2018)
Tomorrow’s agriculture, challenged by increasing global demand for food, scarcity of arable lands, and resources alongside multiple environment pressures, needs to be managed smartly through sustainable and eco-efficient approaches. Modern agriculture has to be more productive, sustainable, and environmentally friendly. While macronutrients such as nitrogen (N), phosphorus (P), potassium (K), and sulfur (S) supplied by mineral fertilizers are vital to crop production, agriculturally beneficial microorganisms may also contribute directly (i.e., biological N2 fixation, P solubilization, and phytohormone production, etc.) or indirectly (i.e., antimicrobial compounds biosynthesis and elicitation of induced systemic resistance, etc.) to crop improvement and fertilizers efficiency. Microbial-based bioformulations that increase plant performance are greatly needed, and in particular bioformulations that exhibit complementary and synergistic effects with mineral fertilization. Such an integrated soil fertility management strategy has been demonstrated through several controlled and non-controlled experiments, but more efforts have to be made in order to thoroughly understand the multiple functions of beneficial microorganisms within the soil microbial community itself and in interaction with plants and mineral resources. In fact, the combined usage of microbial [i.e., beneficial microorganisms: N2-fixing (NF), P-solubilizing, and P mobilizing, etc.] and mineral resources is an emerging research area that aims to design and develop efficient microbial formulations which are highly compatible with mineral inputs, with positive impacts on both crops and environment. This novel approach is likely to be of a global interest, especially in most N- and P-deficient agro-ecosystems. In this review, we report on the importance of NF bacteria and P solubilizing/mobilizing microbes as well as their interactions with mineral P fertilization in improving crop productivity and fertilizers efficiency. In addition, we shed light on the interactive and synergistic effects that may occur within multi-trophic interactions involving those two microbial groups and positive consequences on plant mineral uptake, crop productivity, and resiliency to environmental constraints. Improving use of mineral nutrients is a must to securing higher yield and productivity in a sustainable manner, therefore continuously designing, developing and testing innovative integrated plant nutrient management systems based on relevant biological resources (crops and microorganisms) is highly required.